(untitled) (Research, Society and Development, 2021)
The common bean is one of the crops of high socioeconomic relevance to Brazil. However, the different growing regions of the crop have favored the emergence of pests and diseases, which greatly affect grain yields. The anthracnose of bean is highly damaging to the crop, because losses can be high and/or depreciate the quality of the product making it less attractive to trade. Therefore, the objective of this study was to evaluate the detection of accessions compatible with C. lindemuthianum and the reaction of resistance and susceptibility of 22 traditional accessions of common bean to races 73 and 89 of C. lindemuthianum. In the sanity analysis, we used the incubation test on a germination paper roll, whose seeds were conditioned for 10 days in the BOD at a temperature of 20°C ± 2°. In the evaluation of susceptibility and resistance to the pathogen, races 73 and 89 of C. lindemuthianum were used. The inoculum was obtained from monospore cultures of the respective races previously prepared. The spore suspension was adjusted to an approximate concentration of 1.2 x 106 spores mL-1 of sterile distilled water. The results of the analysis of C. lindemuthianum detection showed that in 81.2% of the accessions no lesions or spores of the pathogen were detected, indicating contamination of the accessions with the pathogen. The reaction of susceptibility and resistance to races 73 and 89 showed a virulence index of 70.58% and 12.5% for the respective races among the analyzed accessions.